Expert consensus on the combined investigation of carpal tunnel syndrome with electrodiagnostic tests and neuromuscular ultrasound. (March 2022) - Pelosi, Luciana; Arányi, Zsuzsanna; Beekman, Roy; Bland, Jeremy; Coraci, Daniele; Hobson-Webb, Lisa D.; Padua, Luca; Podnar, Simon; Simon, Neil; van Alfen, Nens; Verhamme, Camiel; Visser, Leo; et al.
Highlights: Based on expert consensus combining electrodiagnosis and ultrasound is more informative than either modality alone. When electrodiagnostic studies are normal or fail to localize suspected carpal tunnel syndrome, ultrasound adds value. Electrodiagnostic studies add value to ultrasound in quantifying severity of carpal tunnel syndrome and in testing individuals over age 70. Abstract: Expert consensus was sought to guide clinicians on the use of electrodiagnostic tests (EDX) and neuromuscular ultrasound (NMUS) in the investigation of suspected carpal tunnel syndrome (CTS). Consensus was achieved using the Delphi method via three consecutive anonymised surveys of 15 experts and was defined as rating agreement ≥ 80%. The panel agreed that combining EDX and NMUS is more informative than using each modality alone. NMUS adds value in patients with clinically suspected CTS with non-localizing or normal EDX, atypical EDX, failed CTS surgery, polyneuropathy, and CTS suspected to be secondary to structural pathology. The median nerve cross-sectional area should be measured at the site of maximal nerve enlargement, and the nerve should be scanned from mid-forearm to the palm. The group also identified those situations where the wrist-to-forearm area ratio and longitudinal scans of the median nerve should also be obtained. EDX should always be performed to quantify CTS severity and in individuals over age 70. This document is an initial step to guide clinicians on the combined investigation of CTS using EDX and NMUS, to be updated regularly with the emergence of new research.